Beyond the lone voice: how community-based communication restores trust - Yudin, Jacob (Frontiers in Communication, 2025)
Public trust in science remains below pre-pandemic levels, underscoring an urgent need to reevaluate conventional science communication practices. This paper identifies a crucial vulnerability inherent in the common practice of relying on single, authoritative spokespersons. Drawing upon interdisciplinary insights, I propose replacing lone figureheads with community-based expert panels, transparently highlighting areas of consensus as well as legitimate disagreements. This approach fosters greater accountability, reduces personal risks for individual communicators, and portrays science authentically as the dynamic, collaborative, and iterative enterprise that it is. By openly conveying the collective nature of scientific inquiry, the proposed community-panel model can more effectively restore and sustain public trust.